Developing a new Safety Risk Model (SRM) methodology for the GB rail industry. Issue 1 (2nd January 2021) - Gilchrist, Alex; Harrison, Chris
Abstract: This paper presents research recently undertaken by RSSB to develop a new Safety Risk Model (SRM) methodology. The SRM provides a network-wide risk profile for the mainline railway in Great Britain (GB) and has underpinned the industry's evidence and risk-based approach to safety management for the best part of two decades. Firstly, users' requirements were identified, collated and prioritised. The current SRM was then reviewed, summarised and appraised against these requirements to determine areas where there was potential to improve the current methodology. Potential new methodologies were then investigated to determine whether there were any which may enable the new SRM to better meet current user requirements. The feasibility and potential benefits of these alternative methodologies were assessed to determine the best approach for building the new SRM. This paper gives an overview and understanding of the processes that have been carried out in this research and will be of interest to others who may wish to undertake a similar appraisal of their risk models. Abbreviations: ALARP: as low as reasonably practicable; ALCRM: all level crossing risk model; BN: Bayesian network; CBA: cost benefit analysis; ETCS: European train control system; FWI: fatalities and weighted injuries; GB: Great Britain; HAZID: hazard identification; HEM: hazardous event movement accident; HEN: hazardous event non-movement accident; HET: hazardous event train accident; HS2: High Speed 2; PIM: Precursor Indicator Model; RPT: Risk Profile Tool; RSSB: Rail Safety & Standard Board; SMIS: safety management intelligence system; SRM: Safety Risk Model; SWOT: strengths, weaknesses, opportunities and threats